(untitled) (ReAttach Affect Coach Journal, 2025)
NeuroLog [1,2] provides a continuous, patient-led data infrastructure to measure the impact of ReAttach objectively [3], facilitated by specifically trained Affect Coach Online Professionals [4]. Neurolog transforms subjective progress into quantifiable change through: Real-world symptom tracking, Emotional and behavioral analytics, Automated longitudinal comparisons, Integration of qualitative patient voice. Together, these data create a scientifically robust yet human-centered evidence base for the therapeutic value of interventions in Functional Neurological Disorder. This study protocol is the first of several intervention studies using Neurolog to assess changes in symptomatology, beginning with the evaluation of the effectiveness of ReAttach self-regulation techniques [3,4] in FND patients with stress-related disorders.